2018
DOI: 10.1097/iae.0000000000001743
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2d and 3d Video Displays for Teaching Vitreoretinal Surgery

Abstract: Three-dimensional videos may have value in teaching intraocular ophthalmic surgeries. Surgical procedure steps and basic ocular anatomy may have to be reviewed to ensure maximal teaching efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 10 publications
1
40
0
5
Order By: Relevance
“…Chhaya et al recently demonstrated that the use of 3D visualization enhances the learning benefit of intraocular ophthalmic surgeries. [5] In our experience, with the NGENUITY 3D visualization system, the physicians in training were able to see exactly what the surgeon was seeing – at the same depth, with the same focus, and with excellent clarity, which was helpful for surgical training.…”
Section: Discussionmentioning
confidence: 99%
“…Chhaya et al recently demonstrated that the use of 3D visualization enhances the learning benefit of intraocular ophthalmic surgeries. [5] In our experience, with the NGENUITY 3D visualization system, the physicians in training were able to see exactly what the surgeon was seeing – at the same depth, with the same focus, and with excellent clarity, which was helpful for surgical training.…”
Section: Discussionmentioning
confidence: 99%
“…Because all the observers in the operating room can put on polaroid glasses and view exactly the same image as the surgeon with minimal relay time, teaching is enhanced. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…The 3D visualization system has many benefits over the traditional optical microscope. The most significant benefits particular to this procedure are the use of lower illumination levels [ 12 ], improved depth of field [ 13 ], excellent trainee and staff viewing [ 14 ], ergonomics [ 15 ], high recording quality, and more efficient and shorter cases compared to using an indirect ophthalmoscope [ 10 ].…”
Section: Discussionmentioning
confidence: 99%